Inferring the serotype of dengue virus infections based on pre- and post-infection neutralizing antibody titers - Van Panhuis, Willem G (2010)
BACKGROUND: Currently, the only tests capable of determining the serotype of a dengue virus (DENV) infection require sampling during the acute viremic period. No test can accurately detect the serotype of past DENV infections. The standard assay for detecting serotype-specific antibody against DENV is PRNT though the performance of this test continues to be evaluated. METHODS: From a cohort study among schoolchildren in Thailand PRNT were determined in serum samples collected before and after infection. A multinomial logistic regression model was used to infer the serotype of intercurrent DENV infections. Models were validated based on PCR identification of DENV serotypes. RESULTS: The serotype of infection inferred by the model corresponded with PCR in 67.6% of cases and the kappa statistic was 0.479. A model for 35 cases with primary seroconversion correctly identified serotypes of infection in 77.1% of cases compared to 66.9% using a model for 169 cases with secondary seroconversion. The best model using only post-infection PRNT values correctly inferred the serotype of infection in 60.3% of cases. CONCLUSIONS: A statistical model based on both pre- and post-infection PRNT values can be used for inference on the serotype of DENV infections in prospective studies such as vaccine trials.